Surface‐Mediated Interconnections of Nanoparticles in Cellulosic Fibrous Materials toward 3D Sensors. Issue 36 (23rd July 2020) - Yan, Shan; Shan, Shiyao; Wen, Jianguo; Li, Jing; Kang, Ning; Wu, Zhipeng; Lombardi, Jack; Cheng, Han‐Wen; Wang, Jie; Luo, Jin; He, Ning; Mott, Derrick; et al.
Abstract: Fibrous materials serve as an intriguing class of 3D materials to meet the growing demands for flexible, foldable, biocompatible, biodegradable, disposable, inexpensive, and wearable sensors and the rising desires for higher sensitivity, greater miniaturization, lower cost, and better wearability. The use of such materials for the creation of a fibrous sensor substrate that interfaces with a sensing film in 3D with the transducing electronics is however difficult by conventional photolithographic methods. Here, a highly effective pathway featuring surface‐mediated interconnection (SMI) of metal nanoclusters (NCs) and nanoparticles (NPs) in fibrous materials at ambient conditions is demonstrated for fabricating fibrous sensor substrates or platforms. Bimodally distributed gold–copper alloy NCs and NPs are used as a model system to demonstrate the semiconductive‐to‐metallic conductivity transition, quantized capacitive charging, and anisotropic conductivity characteristics. Upon coupling SMI of NCs/NPs as electrically conductive microelectrodes and surface‐mediated assembly (SMA) of the NCs/NPs as chemically sensitive interfaces, the resulting fibrous chemiresistors function as sensitive and selective sensors for gaseous and vaporous analytes. This new SMI–SMA strategy has significant implications for manufacturing high‐performance fibrous platforms to meet the growing demands of the advanced multifunctional sensors and biosensors. Abstract : To create 3D fibrous sensors, surface‐mediated interconnection of bimodally distributed gold–copper alloy nanoclusters and nanoparticles (NPs) is exploited as an effective pathway to fabricate embedded microelectrodes in cellulosic fibrous materials. This pathway is further coupled to surface‐mediated assembly of the NPs to produce chemically sensitive interfaces to targeted gases/vaporous analytes.